Pulmonary Embolism as a Rare Complication of Clomiphene Therapy: A Case Report and Literature Review - Vinod Solipuram; Kishor Pokharel; Temple Ihedinmah (Case Reports in Endocrinology)
Background. Pulmonary embolism (PE) is a medical emergency. Certain medications like oral contraceptives and hormone replacement therapies have been associated with PE. Clomiphene citrate is a selective estrogen receptor modulator, approved for treating infertility in females, but is being used as an off-label therapy in treating male hypogonadism. Very rarely, clomiphene can cause pulmonary embolism. Case Report. A 56-year-old gentleman presented with acute onset shortness of breath and chest discomfort. Upon further workup, he was found to have large volume pulmonary embolism. He was prescribed clomiphene citrate (CC) 2 years ago for hypogonadism. He was started on anticoagulation with improvement in his symptoms, and clomiphene was discontinued. Conclusion. Pulmonary embolism is a rare but potential complication of clomiphene therapy. In male patients with suspected hypogonadism, the risk of serious thromboembolic complications should be discussed before prescribing CC. Patients on CC have to be carefully monitored for serious side effects.